2017
DOI: 10.1093/abbs/gmx072
|View full text |Cite
|
Sign up to set email alerts
|

Isochlorogenic acid A promotes melanin synthesis in B16 cell through the β-catenin signal pathway

Abstract: Isochlorogenic acid A, also called 3,5-dicaffeoylquinic acid (3,5-diCQA), is a widespread phenolic compound in the plant. Recent studies have shown that it has antioxidant and anti-inflammatory activity. In addition, oxidative stress and inflammation induced by solar ultraviolet radiation is a very significant reason for skin depigmentation. Therefore, in this study, we evaluated the effect of 3,5-diCQA on B16 cells and explored its molecular mechanism. Results showed that 3,5-diCQA upregulated intracellular m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 36 publications
0
16
0
Order By: Relevance
“…Our study group have focused on identifying novel compounds in Kaliziri, and have isolated 1,5-diCQA using high performance liquid chromatography (HPLC) and preparative HLPC, which may be the active ingredient ( 38 , 39 ). Previous studies suggested that methyl 3,5-dicaffeoylquinate and 3,5-dicaffeoylquinic acid, two different structural analogues of 1,5-diCQA, induce melanin synthesis ( 40 , 41 ). Therefore, we hypothesized that 1,5-diCQA may have effects on melanin synthesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study group have focused on identifying novel compounds in Kaliziri, and have isolated 1,5-diCQA using high performance liquid chromatography (HPLC) and preparative HLPC, which may be the active ingredient ( 38 , 39 ). Previous studies suggested that methyl 3,5-dicaffeoylquinate and 3,5-dicaffeoylquinic acid, two different structural analogues of 1,5-diCQA, induce melanin synthesis ( 40 , 41 ). Therefore, we hypothesized that 1,5-diCQA may have effects on melanin synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…1,5-DiCQA is a structural analogs of isochlorogenic acid A, which stimulates melanin synthesis via the Wnt signaling pathway ( 41 ). Therefore, the present study examined the effect of 1,5-diCQA on the Wnt signal pathway.…”
Section: Discussionmentioning
confidence: 99%
“…e HEMs were treated with NaHS at the indicated concentration for 24 h and then incubated in normal medium for another 24 mentation diseases such as albinism and vitiligo. Several previous studies have shown some substances have a regulatory effect on melanin synthesis [21][22][23]. Compared with these agents, the therapeutic advantage of H 2 S is that it is a kind of small molecular weight, water-and lipid-soluble intrinsic gasotransmitter that can freely penetrate into the cell membrane to exert a biological effect.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…According to the best of our knowledge, there are no previous reports on the development of a fingerprint study of V. anthelmintica herb profiles to distinguish their geographical origins in various V. anthelmintica herb-producing countries. In the previous studies about this plant, we found that three dicaffeoyl quinic acids (CQAs) play an important role in the treatment of vitiligo [ 23 , 24 ], the 3 CQAs are an isomer and hence there is also the possibility of interchanging each other, and they are high in V. anthelmintica . Therefore, the quantitative determination of the 3 CQAs as marker compounds was studied in this article, and chromatographic fingerprinting was established by combination with a basic conventional analytical, highly precise, accurate, and novel pattern recognition method (HPLC-DAD) for quality control of V. anthelmintica herbs from different countries of origin.…”
Section: Introductionmentioning
confidence: 99%